FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN REMATIK PADA PENDERITA REMATIK DI KELURAHAN VI SUKU WILAYAH KERJA PUSKESMAS TANAH GARAM KOTA SOLOK - Afridon Afridon (Ensiklopedia Education Review, 2020)
Rheumatic disease is a disease affecting the joints and surrounding structures, consisting of more than 100 types. Rheumatoid Arthritis (RA) is a progressive autoimmune disease with chronic inflammation that attacks the musculoskeletal system but can involve the organs and systems of the body as a whole, characterized by swelling, joint pain and destruction of synovial tissue accompanied by movement disorders followed by premature death. This type of research is analytical, with a cross sectional design, where in this study, the dependent and independent variables will be observed at the same time, this method is expected to be known "Factors Associated with Rheumatic Incidence in Rheumatism Patients in Village VI Ethnic Work Area. Puskesmas Tanah Garam Kota Solok ". Based on the results of research conducted on 40 respondents, it can be concluded that there is a relationship between genetics and the incidence of rheumatism, there is a relationship between age and the incidence of rheumatism, there is a relationship between sex and the incidence of rheumatism, there is a relationship between obesity and the incidence of rheumatism and a relationship between lifestyle and incidence rheumatism in Kelurahan VI Tribe, Tanah Garam Public Health Center, Solok City.